Sepsis-associated acute kidney injury and the need for renal replacement therapy: A physician's perspective - Vijoy Kumar Jha; Debasish Mahapatra (Wolters Kluwer Medknow Publications, 2022)
Sepsis associated acute kidney injury is a very common complication and carries unacceptable mortality in the setting of critical illness. Physicians should be very prompt to recognise it an an eartly stage, as providing supporting care early will limit further insults to the kidney. By the time patients seek medical attention, acute kidney injury has already happened. Microvascular dysfunction, inflammation, and metabolic reprogramming are three mechanisms that have been proposed to explain the pathophysiology of acute kidney injury associated with sepsis. The role of early renal replacement therapy /blood purification technique is still controversial. We need more studies to better understand the complex pathophysiology of this complication and translate these findings into potential treatment strategies. In this review, new definitions of sepsis and acute kidney injury, risk factors, pathophysiology and management strategies of sepsis- associated acute kidney injury are being discussed.